Potentiostatic Deposition and Characterization of Cuprous Oxide Thin Films. (17th April 2013) - El-Shaer, A.; Abdelwahed, A. R.
Abstract : Electrodeposition technique was employed to deposit cuprous oxide Cu2 O thin films. In this work, Cu2 O thin films have been grown on fluorine doped tin oxide (FTO) transparent conducting glass as a substrate by potentiostatic deposition of cupric acetate. The effect of deposition time on the morphologies, crystalline, and optical quality of Cu2 O thin films was investigated.